A multimodal analysis of a brand ambassador post on social media - Natalia Faradheta Putri; Altobeli Lobodally (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
The selection of brand ambassadors for advertising campaigns, particularly in social media, is widely popular, especially when Korean celebrities are appointed as models. Addressing a research gap regarding the multimodal analysis of local brand ambassadors, this study diverges from prior research that predominantly concentrates on Korean brand ambassadors. Utilizing Instagram posts from the @aliciabeverlyw account, who happens to be a brand ambassador of Kalbis Institute and a social media influencer, the study examines a dataset comprising nine image-based posts. Employing multimodal analysis, the study seeks to explain the three metafunctions of the advertisements, drawing upon Kress and Leeuwen's social semiotics theory. The result indicated that the brand ambassador established trustworthiness with the audience at the ideational level. She fostered a sense of familiarity and similarity with the audience within the interpersonal metafunction. Lastly, she introduced product match-up and product transfer elements to the audience at the textual metafunction level. To sum up, the study concluded that the brand ambassador utilized multimodal metafunctions as a strategy to build rapport with the audience.